Producing Liminal Spaces: Borders, Sovereignty, and Governance in the Gilgit Agency. - Qayyum, Amna. (2017)
Abstract: Since 1947 the people of Gilgit-Baltistan have called for integration within the Pakistani state and the extension of fundamental rights to them. This thesis examines how the region's liminality stems from the ambiguities in sovereignty in the colonial and post-colonial period. British policymakers chose to keep the political status and territorial limits of the Gilgit Agency undefined, leading to its position as an anomalous space within the patchwork of empire. Legally part of the princely state of Jammu and Kashmir, administered by the British, and ruled by local leaders - sovereignty was not monolithic in the Gilgit Agency. Even though the Agency was a cartographically unified entity, its internal dynamics prevented the imposition of centralized authority. Although part of the princely state of Jammu Kashmir, the Gilgit Agency was administered and governed by the British. Much like other parts of the Indian frontier, the British ruled through `natural leaders'. By subsidizing these rulers heavily the British fashioned a mode of governance that was primarily concerned with ordering these societies, rather than incorporating them into debates over rights and citizenship. The local leaders continued to exert substantial authority over their subjects. Sovereignty in the Gilgit Agency was not rooted in the Westphalian notion of asserting authority and jurisdiction over territory, but rather in the power to "declare the colonial exception". The nature of sovereignty was then divisible, and at times ambiguous. The colonial government used the ambiguous nature of this sovereignty to legally administer, but not possess the Gilgit Agency. The `handing back' of the Gilgit Agency to the Dogras in 1947 meant its incorporation into a princely state that had never asserted complete political authority over it before. With the linking of Gilgit-Baltistan to the Kashmir issue, the area has been placed in permanent limintality until the resolution of the Kashmir dispute. Since Pakistan cannot legally claim Gilgit-Baltistan as its territory, it has used this pretext to place the region in a state of permanent exception until the issue of sovereignty is resolved. The Kashmir dispute has been used as a premise to deny rights and self-governance, and ensure a strong grip on Gilgit-Baltistan. With the tying of the Gilgit Agency to the Kashmir issue, the Pakistani state continued to treat it as a colonial outpost and adopted the same political, legal, and economic policies as the British imperial government up till the 1970s. The ambiguities in sovereignty still continued since the Gilgit Agency and Baltistan were legally disputed territory. The post-colonial state used this pretext to deny basic constitutional rights to the people, deprive them from participating in decision-making at the center, and provide them limited powers of self-governance. In 1970 limited reforms were made, and the Gilgit Agency and Baltistan were formed into an administrative unit called the Northern Areas. Although these two regions shared certain similarities, they had never been politically united in pre-colonial or colonial times. In certain historiography there has been a tendency to examine these regions as one entity - however such works tend to read back in time, assuming the Northern Areas as a historical reality. Whereas the states comprising the Gilgit Agency were linked more closely to Chitral and Badakshan, Baltistan had strong ties to Tibet and Ladakh. The latter was also not incorporated into British structures of governance unlike the Gilgit Agency. Given their varied historical trajectories, this thesis will then focus on the geographic area comprising the Gilgit Agency. The first chapter "Creating Spaces" examines imperial conceptions of the northern frontier of India, and how this led to the establishment of a political entity labeled as the Gilgit Agency. At the apogee of the so-called `Great Game' mapping was used as a tool to create spaces, secure strategic imperatives of trade and communication, and partake in imperial rivalries. However, an exercise in mapping alone was not enough to assert political authority over the Gilgit Agency. "Managing the Colonial Frontier" then observes how a new administrative structure and military operations were employed to secure control over this area. While examining the nature of colonial governance and statecraft in the Gilgit Agency, it becomes clear that the local leaders of these states still exercised a substantial amount of power over their subjects. Throughout the course of its existence the exact territorial extent and political status of the British Indian Gilgit Agency was never clearly defined. This ambiguity, combined with a clear sidelining of Dogra authority, would then contribute to the liminal status occupied by the Gilgit Agency. The final chapter, "Postcolonial Liminality" traces the political trajectory of the Gilgit Agency/Northern Areas/Gilgit-Baltistan since 1947. Following the Gilgit Rebellion (1947) the people of this region called for integration within the Pakistani state. However the Kashmir dispute was always used as an excuse to delay constitutional recognition and the provision of political and electoral rights. I will argue that current concerns over power generation and Chinese influence in Gilgit-Baltistan contributed to the recently enacted Empowerment and Self-Government Order, 2009 which promises to provide full internal autonomy and province-like status to Gilgit-Baltistan, without actually conferring the status of a constitutional province on it. The imperial project of teritorialization - which was an attempt to assert political authority by demarcating boundaries - was never fully completed in the Gilgit Agency. Much like the oddly defined and administered Gilgit Agency of colonial India, the Gilgit-Baltistan of today waits for autonomy, representation, and rights. In some ways the process of decolonization started in 1947, is still ongoing in Gilgit-Baltistan.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of History.; Advisors: Ayesha Jalal, and Kris Manjapra.; Keywords: History, and South Asian studies.